Analysis of Implementation of The Acceleration of Midwife Education Program through The Mechanism of Recognition of Past Learning (RPL) at Poltekkes Kemenkes Padang - Helpi Nelwatri; Mardiani Bebasari; Nurhizrah Gistituati3; Rusdinal (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Community needs for quality health services are increasing, in line with developments happening in the world today. Health workers are one of the main factors in health service efforts so that it is necessary to improve the quality of health workers. One of the efforts to improve the quality of health workers is through education. Recognition of Past Learning (RPL) as outlined in the Minister of Health Regulation Number 41 of 2016 concerning the Program for Accelerating the Improvement of Education Qualifications for Health Workers. knowing how to implement the Accelerated Nursing Education Program through the Recognition Mechanism of Past Learning (RPL) at Poltekkes Kemenkes Padang, using qualitative research methods with research designs using the Rapid Assessment Procedure (RAP) or rapid assessment procedures. Research result that the implementation of the Midwifery Education Acceleration Program through the RPL Mechanism at the Health Polytechnic of the Ministry of Health Padang has been going well despite experiencing several obstacles in program socialization and technical implementation of learning related to the status of students' study permit.